واقع تعليم اللغة العربية وتعلّمها في نيجيريا وقضية اتجاهات جديدة: Indeed, teaching the Arabic language and learning it in Nigeria is a new trend - Sirajudeen, Adam Adebayo; Rufai Aminullahi, Ahmad (SIBAWAYH Arabic Language and Education, 2023)
لقد مرّ للتعليم العربي تعليمها وتعلّمها في نيجيريا بأطوار تاريخيّة متعاقبة تغيّرت معها أغراض التعليم منها؛ الغرض الديني المحض، ثمّ تدهور الوضعُ إبّان فترة الاستعمار البريطاني وما بعدها إلى اليوم فأصبحت اللغة العربية تتعلّم للغرض الثقافي والاجتماعي، ويندرج ضمن هذا الغرض الذي جعلت العوامل الحديثة (الدبلوماسية، الاقتصادية، والاجتماعية) أهدافا وأغراضا أخرى للغة العربية، وأن لبست اللغة العربية اتجاهات جديدة في تعليمها وتعلّمها، فأصبح أهداف التعليم العربي في نيجيريا كغيرها من الدول خارج الحقل الديني الذي هو هدفه الأساسي، فبلورة هذا البحث المتواضع واقع التعليم العربي وتعلّمه في نيجيريا واتجاهاته الجديدة، كما يزمع البحث في استعراض أغراض التعليم العربي في نيجيريا عبر العصور من حيث الاستمرار والتغيّر، وانطلاقا من هنا يقوم هذا البحث بدراسة تلك التغيّرات التي طرأت على اللغة العربية ووضعها الراهن في نيجيريا مع مراعاة التحوّلات المنظوريّة في اتجاهاتها الجديدة ومراحلها المختلفة، ويظهر راهنيّة اللغة العربية في نيجيريا. ويتمحور هذا البحث على هذه العناوين الجانبية كالتالي: المقدمة، استعراض أغراض التعليم العربي في نيجيريا عبر العصور، واقع التعليم العربي اليوم في نيجيريا، اتجاهات جديدة في تعليم اللغة العربية وتعلمها في نيجيريا، ثم مستقبل التعليم العربي في نيجيريا فالخاتمةHe passed the Arabic education and learned it in Nigeria in historical stages and subsequently changed with it the educational purposes of it; The religious purpose, then the deterioration of the situation during the period of British colonialism and after that until today, the Arabic language became learned for cultural and social purposes, and it is included in this purpose that modern factors (diplomatic, economic, and social) made other goals and purposes for the Arabic language, and that the Arabic language changed new directions In its education and learning, the goals of Arabic education in Nigeria, like other countries, have become outside of religious law, which is its primary goal. The result of this humble research is the reality of Arabic education and learning in Nigeria and its new trends, as well as the research in reviewing the goals of Arabic education in Nigeria through the ages in terms of continuity and change. , and starting from here, this research will study those changes that have occurred in the Arabic language and its current state in Nigeria, taking into account the perspective changes in its new directions and different stages, and show the progress of the Arabic language in Nigeria. This research is focused on these side titles as follows: Introduction, review of the purposes of Arabic education in Nigeria through the ages, the reality of Arabic education today in Nigeria, new trends in Arabic education and learning in Nigeria, then the future of Arabic education in Nigeria Conclusion.Keyword: indeed, Teaching the Arabic language, New trends, Nigeria, to learn